E2β stimulates ovine uterine artery endothelial cell H2S production in vitro by estrogen receptor-dependent upregulation of cystathionine β-synthase and cystathionine γ-lyase expression. Issue 2 (2nd October 2018) - Lechuga, Thomas J; Qi, Qian-rong; Kim, Theresa; Magness, Ronald R; Chen, Dong-bao
Abstract: Endogenous hydrogen sulfide (H2 S) is a potent vasodilator and proangiogenic second messenger synthesized from L-cysteine by cystathionine β-synthase (CBS) and cystathionine γ-lyase (CTH). Estrogens are potent vasodilators that stimulate H2 S biosynthesis in uterine arteries (UA) in vivo; however, the underlying mechanisms are unknown. We hypothesized that estrogens stimulate H2 S biosynthesis in UA endothelial cells (UAEC) via specific estrogen receptor (ER)-dependent mechanisms. In cultured primary UAEC, treatment with estradiol-17β (E2 β) stimulated CBS and CTH mRNAs and proteins in a time- and concentration-dependent fashion. As little as 0.1 nM E2 β was effective in increasing CBS and CTH expressions and these stimulatory effects maximized with 10–100 nM E2 β at 48–72 h. E2 β also activated CBS and CTH promoters in UAEC, leading to CBS and CTH expression. Treatment with E2 β stimulated H2 S production, which was blocked by specific inhibitors of either CBS or CTH and their combination and the ER antagonist ICI 182780. Treatment with either specific agonist of ERα or ERβ stimulated both CBS and CTH mRNA and protein expressions and H2 S production to levels similar to that of E2 β. Specific antagonist of either ERα or ERβ blocked E2 β-stimulated CBS and CTH mRNA and protein expressions and H2 S production. Combinations of either ERα or ERβ agonists or their antagonists had no additive effects. Thus, E2 β stimulates H2 S production by upregulating CBS and CTH mRNA and protein expressions through specific ERα or ERβ-dependent CBS and CTH transcription in UAEC in vitro. Abstract : Estradiol-17β stimulates uterine artery endothelial cell hydrogen sulfide biosynthesis.